CLINICAL-EPIDEMIOLOGICAL PROFILE OF OBSTETRIC INCIDENTS HANDLED BY THE MOBILE EMERGENCY SERVICE (SAMU) IN ANÁPOLIS – GOIÁS (CIPEEX, 2025)
Objective: To evaluate the clinical and epidemiological profile of obstetric services provided by the SAMU in Anápolis – Goiás during January, March, and April 2023. Methodology: This is an epidemiological, descriptive, cross-sectional, and retrospective study. It was conducted in the municipality of Anápolis – GO, using SAMU-192 incident reports from the first quarter of 2023 as the information source. Results: A total of 145 obstetric incidents were recorded. Most occurred in January, involving women aged 25 to 30 years, predominantly in the afternoon and on weekends. The majority of incidents originated at home. Additionally, contractions were the most frequently reported obstetric reason in February and March, while abdominal/pelvic pain predominated in January. Conclusion: Obstetric incidents accounted for a small portion of total SAMU cases. The patients were mostly young women aged 25–30, with services occurring mainly in the afternoon, on weekends, and at home, and contractions being the primary reason for calls. The study highlights SAMU’s importance in pre-hospital support for pregnant women and its crucial role in obstetric public health.
Keywords: Emergency Medical Services; Obstetrics; Epidemiological Studies; Pre-Hospital Services